Search Frictions and Product Design in the Municipal Bond Market - Brancaccio, Giulia; Kang, Karam (Econometrica, 2025)
This paper shows that product design shapes search frictions and that intermediaries leverage this channel to increase their rents in the context of the U.S. municipal bond market. The majority of bonds are designed via negotiation between a local government and its underwriter. They are then traded in a decentralized market, where the underwriter often also acts as an intermediary. Exploiting variations in state regulations that limit government officials' conflicts of interest, we provide evidence that the underwriter benefits from designing and trading complex bonds, which induces an increase in search frictions. Interestingly, a simpler bond may not necessarily benefit the government, as bond complexity affords flexibility in debt repayment. Motivated by these findings, we build and estimate a model of bond origination and trading to quantify the welfare implications of a policy mandating bond standardization.